Atipikus szerződések Magyarországon és Szerbiában - Papp, Tekla; Dudás, Attila (Debreceni Jogi Műhely, 2013)
The paper analyzes the notion and types of atypical contracts, primarily in the Hungarian andSerbian law, but also in wider, European perspective. The analysis sheds light on the differentterms used in different legal systems to denominate contracts that do not fit explicitly into therange of nominate contracts, that is into the range of contract-types envisaged by the civilcode or code of obligations, respectively. According to the Hungarian legal literature, all civillaw contracts are divided into two main groups: nominate and innominate contracts. Theformer group is further divided into the categories of typical and atypical contracts, while thelatter into the categories of mixed contracts and de facto innominate contracts.The authors conclude that there is a tendency in Europe, both in the jurisprudence, thelegislation and the application of law, to create a unified and coherent law of contracts, whichaffects the range of atypical contracts as well. Most notably, the Draft Common Frame ofReference, the normative proposal of the Study Group on a European Civil Code and theResearch Group on EC Private Law (Acquis Group), contains model rules on franchise, timesharing,commercial agency and treatment contracts, just as rules on electronic commerce, onthe one hand. The legislation of the European Union, on the other, aims at the highest possiblelevel of harmonisation of laws which, from the aspect of protection of consumers andcompetition law, affects the range and statutory content of atypical contracts. Finally, thepaper refers to a series of decisions of the Court of Justice of the European Union that tacklecertain features of the atypical contracts, whereby the Court in the determination of issues ofcontract law applies a rather functional approach.